Methods for estimating the density of Elaphostrongylus rangiferi Mitskevich (Nematoda, Metastrongyloidea) larvae in faeces from reindeer, Rangifer tarandus L. - Halvorsen, Odd; Wissler, K. (Rangifer, 1983)
A method for estimating the density of Elaphostrongylus rangiferi larvae in reindeer faeces that have been deep frozen is described. The method involves the use of an inverted microscope with plankton counting chambers. Statistical data on the efficiency and sensitivity of the method are given. With fresh faeces, the results obtained with the method were not significantly different from those obtained with the Baermann technique. With faeces that had been stored in deep freeze, the method detected on average 30 per cent more larvae than the Baermann technique. Metoder for å estimere tettheten av hjernemarklarver i avføring fra reinsdyr. Abstract in Norwegian / Sammendrag: En metode for å estimere tettheten av hjernemarklarver i avføring som har vært dypfryst blir beskrevet. Anvendelse av et invertert mikroskop med plankton tellekammer inngår i metoden. Det blir gitt statistiske data for metodens effektivitet og følsomhet. Ved undersøkelse av fersk avføring skilte ikke de resultatene metoden ga seg fra de som ble oppnådd med Baermanns metode. Ved undersøkelse av avføring som hadde vært lagret dypfrosset ga metoden i gjennomsnitt 30 prosent flere larver enn Baermanns metode.